Improving Students’ Reading Ability through Instagram for Vocational High School Student - Ananda, Ahmad Dhea (Universitas Negeri Surabaya, 2023)
This study aims to explain improving reading comprehension skills through Instagram media. The method used is a quasi-experiment method with a non-equivalent control design. The sample in this study were 57 students of class XI vocational high students in the 2021/2022 academic year with an experimental class of Building Drawing Engineering students 1 which has total 29 students and a Building Drawing Engineering 2 control class totaling 28 students. The results of the independent sample T test with a significance level of 0.98 > 0.05, then ha is accepted so that Ho is rejected and Ha can be accepted, so it can be concluded that there is a significant influence in the use of Instagram media on student’s reading comprehension skills. Instagram is media which proper to use in the learning process because it's able to improve student’s reading comprehension skills. Because Instagram as a social media has a lot of content and account to make students attract and there are some items such as pictures, videos, and long video reels.